High-performance liquid chromatographic purification and capillary electrophoresis quantification of the chemokine stromal cell-derived factor-1 - Arcelloni, Cinzia; Aiuti, Alessandro; Cipponi, Arcadi; Paroni, Rita (Journal of chromatography. B, Biomedical sciences and applications, 1999)
Chemokines are members of the chemotactic cytokines family implicated in various immunoregulatory functions. The CXC–chemokine stromal cell derived factor-1 (SDF-1α) was purified from the culture medium of murine bone marrow stromal cell line (MS-5) by affinity and reversed-phase liquid chromatography. Yield and purity were assessed by capillary electrophoresis (CE) with reference to the human SDF-1α from recombinant DNA technology. CE technique was useful to evaluate the purity of human SDF-1α from chemical synthesis and to resolve murine and human SDF-1α, differing by only one amino acid. Chemotactic activity of the murine SDF-1α was tested on the basis of CE quantification.